Y‐site administration of electrolyte solutions and injectable acetaminophen—A physical compatibility study with combinations frequently used in pediatric intensive care and anesthesia. Issue 1 (19th October 2022) - Kleinlein, Mona; Marschler, Stephanie; Neininger, Martina Patrizia; Hoeckel, Michael; Bertsche, Thilo
Abstract: Aim: Determination of the physical compatibility of acetaminophen and two different electrolyte solutions (an isotonic, balanced electrolyte solution and a hypotonic, glucose containing electrolyte solution) with drugs frequently used in routine pediatric intensive care. Methods: Analytical investigations for frequently used combinations without pre‐existing data were performed. Visual and microscopic observations according to the European Pharmacopeia as well as pH measurements and ultraviolet visible spectrometry at wavelengths of 350, 410 and 550 nm were conducted to analyze physical compatibility. All measurements were performed immediately after mixing as well as 1, 4, and 24 h after. Results: In total, 42 combinations were analyzed. Visual incompatibilities were found with pantoprazole and diazepam with both electrolyte solutions. For furosemide, a particle formation in mixture with the hypotonic glucose‐containing electrolyte solution and a change in pH ≥ 0.5 after 24 h with both electrolyte solutions were observed. Ampicillin, cefuroxime, diazepam, furosemide, linezolid, meropenem, and pantoprazole showed an aberration of the absorbance ≥0.04 (350 nm/410 nm) or ≥0.01 (550 nm) in the photometric measurements with the electrolyte solutions. For acetaminophen, a physical incompatibility was observed with ampicillin, diazepam, furosemide, and pantoprazole. Conclusion: Most of the analyzed combinations showed no signs of physical incompatibility and may therefore be administered via the same Y‐site. However, diazepam, furosemide, and pantoprazole should not be administered simultaneously with acetaminophen or both electrolyte solutions.